ROLE OF PANCHAKARMA IN PARKINSONS DISEASE - A CASE STUDY - Swamy, Vishal Karthik; M. Goud, Kiran.; Deshpande, Swati.; M J, Supreeth; K.N, Vinaykumar. (International Journal of Ayurveda and Pharma Research, 2017)
Parkinsons disease is a degenerative disorder of the central nervous system. The motor symptoms of Parkinsons disease result from the death of dopamine-generating cells in the substantia nigra, a region of the midbrain; the cause of this cell death is unknown. Early in the course of disease symptoms include (1) shaking (tremor) (2)  rigidity (3) slowness of movement  (bradykinesia) and (4) difficulty with walking and gait (postural instability). Later, cognitive and behavioral problems may arise, with dementia commonly occurring in the advanced stages of the disease. Other symptoms include sensory, sleep and emotional problems.In Ayurveda, most of the diseases of the Vata are essentially the conditions of degenerative diseases of the nervous system. Kampa vata is one condition which is caused by imbalance of Vata. The treatment of Kampavata consists of both internal and external administration of drugs in different forms aimed to reverse the Vata imbalance. Here a case of 75 years male patient presented with tremors in both hands and postural instability and the pathology of which is to be identified with Dhatukshayaja Vata Vyadhi which is provisionally diagnosed as Kampavata and its line of treatment was adopted based on Nirupasthambita Vata Vyadhi Chikitsa. The present case reveals certain set of Panchakarma modalities of treatments showing significant improvement in the symptoms of Parkinsons disease without causing any side effects.